2021
DOI: 10.1186/s13287-021-02559-4
|View full text |Cite
|
Sign up to set email alerts
|

CD146 controls the quality of clinical grade mesenchymal stem cells from human dental pulp

Abstract: Background Human mesenchymal stem cells from dental pulp (hMSC-DP), including dental pulp stem cells from permanent teeth and exfoliated deciduous teeth, possess unique MSC characteristics such as expression of specific surface molecules and a high proliferation rate. Since hMSC-DP have been applied in numerous clinical studies, it is necessary to establish criteria to evaluate their potency for cell-based therapies. Methods We compared stem cell p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 69 publications
(93 reference statements)
1
26
0
Order By: Relevance
“…Higher expression of CD105 might be explained by the fact that hPL is rich in several growth factors, including insulin-like growth factor 1 (IGF-1), transforming growth factor-beta (TGF-β1, TGF-β2). Ma et al concluded that the expression level of CD146 showed a positive correlation with proliferation, differentiation, and immunomodulation, suggesting that CD146 can serve as a surface molecule to evaluate the potency of human dental pulp stem cells cultivated in the serum-free medium [ 51 ]. To summarize all the above, hNDP-SCs seem more affected by changes in serum-free growth medium than other mesenchymal stem cells, and hPL keeps hNDP-SCs less differentiated and prepared for wider differentiation into mature cells lines.…”
Section: Discussionmentioning
confidence: 99%
“…Higher expression of CD105 might be explained by the fact that hPL is rich in several growth factors, including insulin-like growth factor 1 (IGF-1), transforming growth factor-beta (TGF-β1, TGF-β2). Ma et al concluded that the expression level of CD146 showed a positive correlation with proliferation, differentiation, and immunomodulation, suggesting that CD146 can serve as a surface molecule to evaluate the potency of human dental pulp stem cells cultivated in the serum-free medium [ 51 ]. To summarize all the above, hNDP-SCs seem more affected by changes in serum-free growth medium than other mesenchymal stem cells, and hPL keeps hNDP-SCs less differentiated and prepared for wider differentiation into mature cells lines.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the clinical application of hDPSCs has started in dental pulp regeneration of injured teeth [ 32 ]. Recently, quality-controlled clinical-grade hDPSCs were manufactured for regenerative medicine applications [ 33 , 34 ].…”
Section: Characterization Of Hdpscsmentioning
confidence: 99%
“…CD146 is usually coexpressed with CD73, CD90, CD105, and CD44 on pericytes located outside of capillaries and microvessels in various tissues, such as the muscles, adipose tissue, BM and placenta ( Crisan et al, 2008 ). Several studies suggest that CD146 identifies MSCs with multidirectional differentiation potential ( Ma et al, 2021 ). Compared with CD146 - cells, CD146 + cells showed the potential to differentiate into adipocytes, chondrocytes, and osteoblasts, while CD146 - cells did not ( Baksh et al, 2007 ).…”
Section: Characteristics Of Several Odontogenic Msc Subpopulationsmentioning
confidence: 99%